2018
DOI: 10.24095/hpcdp.38.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of the ‘new’ ParticipACTION: overview and introduction of the special issue

Abstract: ParticipACTION is the Canadian physical activity communications and social marketing organization first launched in the fall of 1971 and then ceased operations in 2001. ParticipACTION was relaunched in 2007. Framed as a public health natural experiment, evidence was collected from a population-based survey of knowledge, awareness, understanding of physical activity, and physical activity levels among Canadians (individual level), and key informant surveys and interviews examining capacity, readiness and advoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…ParticipACTION is a social marketing and communications organization that has promoted physical activity in Canada for most of the past 45 years. 13,14 After a brief hiatus, it was relaunched in 2007. We found that approximately 20% of Canadians were aware of ParticipACTION unprompted and 82% were aware when prompted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ParticipACTION is a social marketing and communications organization that has promoted physical activity in Canada for most of the past 45 years. 13,14 After a brief hiatus, it was relaunched in 2007. We found that approximately 20% of Canadians were aware of ParticipACTION unprompted and 82% were aware when prompted.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for this shift in awareness is that the relaunched ParticipACTION focused much of its communication efforts, during 2007 and 2014, on the parents of inactive children. 13 Thus, the organization's cam paigns and messages may have resonated with Canadian adults who were not neces sarily seeking to change their own physical activity, but rather that of their children. To address this explanation, we adjusted for child status in our logistic regressions and still found a negative association between LTPA status and awareness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ParticipACTION has played a leading role in mass media campaigns for physical activity since relaunch, 21,22 another strategic priority was knowledge exchange with physical activ ity organizations. 23 It could be that ParticipACTION needs to make their core activities apparent to organizations by devoting more time to sharing knowledge products with the ParticipACTION Partner Network, and showcasing current activi ties that may enhance capacity to deliver physical activity programming.…”
Section: Discussionmentioning
confidence: 99%